Analisis Ergonomi Pengaruh Beban Kerja Terhadap Kelelahan Pada Pekerja Pembuatan Batu Bata Secara Manual - Yusuf, Muhammad; Widuri Asih, Endang; Rachmawati, Yuliana; Darmawan, Sigit (Jurnal Teknologi, Fakultas Teknik, Universitas AKPRIND Indonesia, 2024)
Brick is a material that can be used as a building material to make houses, multi-storey buildings and so on. Making bricks manually cannot be separated from the risk of fatigue due to the workload carried out in the brick making process repeatedly. This research identifies and analyzes the effect of workload on work fatigue, determining the level of work fatigue on the workload of manual brick making workers. The population of this study was all 32 male workers, by determining Body Mass Index, determining cardiovascular load, determining workload and determining work fatigue. Data processing and analysis techniques were carried out using multiple linear regression tests. Based on the research results, it shows that there is a significant influence between workload and work fatigue in manual brick making workers, it is known that the value of p = 0.000 or smaller than 0.05 (p < 0.05), and the average level is large. work fatigue is 62.5 with the work fatigue category being moderate.